2009
DOI: 10.1073/pnas.0904309106
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the C-terminal domain of transcription factor IIB from Trypanosoma brucei

Abstract: In trypanosomes, the production of mRNA relies on the synthesis of the spliced leader (SL) RNA. Expression of the SL RNA is initiated at the only known RNA polymerase II promoter in these parasites. In the pathogenic trypanosome, Trypanosoma brucei, transcription factor IIB (tTFIIB) is essential for SL RNA gene transcription and cell viability, but has a highly divergent primary sequence in comparison to TFIIB in well-studied eukaryotes. Here we describe the 2.3 Å resolution structure of the C-terminal domain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…Initially, a USE-binding complex was characterized, which consisted of three SNAP c subunits, TRF4, a clear ortholog of the small TFIIA subunit (TFIIA-2), and a sixth protein whose sequence conservation was too weak to identify it unequivocally as the second, larger TFIIA subunit (13,40). Subsequently, a TFIIB ortholog which deviates substantially in sequence and structure from its human counterpart was identified (20,34,39). The identification of TFIIA-2 and TFIIB suggested that trypanosomes harbor a full set of GTFs.…”
mentioning
confidence: 99%
“…Initially, a USE-binding complex was characterized, which consisted of three SNAP c subunits, TRF4, a clear ortholog of the small TFIIA subunit (TFIIA-2), and a sixth protein whose sequence conservation was too weak to identify it unequivocally as the second, larger TFIIA subunit (13,40). Subsequently, a TFIIB ortholog which deviates substantially in sequence and structure from its human counterpart was identified (20,34,39). The identification of TFIIA-2 and TFIIB suggested that trypanosomes harbor a full set of GTFs.…”
mentioning
confidence: 99%
“…The fact that Tb RNAPII was reported to interact with ENF but is not seen here may reflect interference by the GST-tag with certain protein interactions [39]. Curiously, the crystal structure of Tb TFIIB reveals the trypanosome factor has additional structure relative to TFIIB from higher eukaryotes [13]. It is speculated that these extra regions allow for interactions with trypanosomatid-specific factors.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the trypanosomatid general transcription factor TFIIB is divergent in its sequence [11, 12] and the crystal structure reveals the presence of extra helices and loops speculated to participate in trypanosome-specific protein interactions [13]. The composition of Tb TFIIH was examined and found to contain essential subunits unique to the parasite, while lacking the cyclin-activating kinase [14, 15].…”
Section: 1 Introductionmentioning
confidence: 99%
“…The divergent TFIIB from the parasite Trypanosoma brucei lacks an extensive basic surface for promoter binding, and it is also devoid of the structural and sequence features for interaction with BRE u , which may account for the observed bidirectional transcription [3841]. Widespread divergent transcription has recently been reported for active promoters in other species including mammals and yeast [42, 43].…”
Section: Initiation Of Transcriptionmentioning
confidence: 99%